Diversity of sialic acids and sialoglycoproteins in gametes and at fertilization - Fliniaux, Ingrid; Marchand, Guillaume; Molinaro, Caroline; Decloquement, Mathieu; Martoriati, Alain; Marin, Matthieu; Bodart, Jean-François; Harduin-Lepers, Anne; Cailliau, Katia (Frontiers in Cell and Developmental Biology, 2022)
Sialic acids are a family of 9-carbon monosaccharides with particular physicochemical properties. They modulate the biological functions of the molecules that carry them and are involved in several steps of the reproductive process. Sialoglycoproteins participate in the balance between species recognition and specificity, and the mechanisms of these aspects remain an issue in gametes formation and binding in metazoan reproduction. Sialoglycoproteins form a specific coat at the gametes surface and specific polysialylated chains are present on marine species oocytes. Spermatozoa are submitted to critical sialic acid changes in the female reproductive tract facilitating their migration, their survival through the modulation of the female innate immune response, and the final oocyte-binding event. To decipher the role of sialic acids in gametes and at fertilization, the dynamical changes of enzymes involved in their synthesis and removal have to be further considered.